Physiological predictors of peak velocity in the VAM-EVAL incremental test and the role of kinematic variables in running economy in triathletes - Montraveta, J.; Fernández-Jarillo, I.; Iglesias, X.; Feldmann, A.; Chaverri, D. (Sports, 2025)
This study examined the influence of physiological parameters on peak velocity (Vpeak) and of kinematic variables on running economy (RE) during an outdoor incremental VAM-EVAL test completed by eleven national-level triathletes. Maximal oxygen uptake (VO2max), ventilatory thresholds, RE, and minimum muscle oxygen saturation (SmO2min) were obtained with a portable gas analyzer and near-infrared spectroscopy (NIRS), while cadence, stride length, vertical oscillation, and contact time were recorded with a foot-mounted inertial sensor. Multiple linear regression showed that VO2max and SmO2min together accounted for 86% of the variance in Vpeak (VO2max: r = 0.76; SmO2min: r = -0.68), whereas RE at 16 km·h-1 displayed only a moderate association (r = 0.54). Links between RE and kinematic metrics were negligible to weak (r = 0.38). These findings confirm VO2max as the primary determinant of Vpeak and suggest that SmO2min can be used as a complementary, non-invasive marker of endurance capacity in triathletes, measurable in the field with portable NIRS. Additionally, inter-individual differences in cadence, stride length, vertical oscillation, and contact time suggest that kinematic adjustments are not universally effective but rather highly individualized, with their impact on RE likely depending on each athlete`s specific characteristics.